Construction and Characterization of Soybean Isolate Protein-Polysaccharide-Starch Salt-reducing Gel System - Siqi YANG; Qianqian ZHANG; Yingru XU; Zhixiong LIN; Yi ZHANG; Baodong ZHENG; Hongliang ZENG (Shipin gongye ke-ji)
In this paper, salt-reducing gel based on soybean protein isolate-polysaccharide-cassava starch was constructed with konjac glucomannan, carrageenan and xanthan gum, respectively. The results showed that soy protein-Konjac glucomannan condensates and soy protein-carrageenan condensates had strong retention capacity for sodium ions on pig tongue, which was conducive to salty perception. Electron tongue analysis showed that compared with carrageenan and xanthan gum, the salt-reducing gel system of soy protein isolate-Konjac glucomannan-starch (ST+SPI-KGM+1.5% NaCl) and 2% NaCl starch gel (ST+2% NaCl) had the most similar saltiness. In microstructure, SPI-KGM and starch were cross-linked to form a continuous and dense network structure. X-ray energy dispersion spectroscopy showed that sodium ions in ST+SPI-KGM+1.5% NaCl presented an uneven distribution. Compared with 2% NaCl starch gel, the water holding capacity and texture properties (hardness, chewiness and cohesiveness) of soybean protein-polysaccharide-starch salt-reducing gel were significantly increased (P<0.05), among which ST+SPI-KGM+1.5% NaCl had the best effect. The concentration of NaCl by soybean isolate protein-polysaccharide complex condensates to regulate the uneven distribution of salt in the food substrate could reduce 25% salt content without reducing the saltiness. This study developed a salt reduction gel system with uneven salt distribution while maintaining its texture perception, providing a new idea for reducing the salt content of starch-based solid foods.